Habermas and Induced Pluripotent Stem Cells: An Ethical Analysis - Wirth, Mathias (Ethical perspectives, 2024)
In his 2001 book The Future of Human Nature, Habermas raised serious objections to the scientific use of embryonic stem cells. Since then, biotechnology has made great strides, and innovative technologies have come to fruition. In particular, it is now possible to reprogram somatic cells to form induced pluripotent stem cells (iPSCs). This paper examines whether or not the objections that Habermas raised at the time about producing and using embryonic stem cells (ECSs) also apply to iPSCs. To this end, we begin by reviewing biological findings concerning iPSCs and the current bioethical discussion around them, before giving a recap of Habermas’s main argument and, finally, connecting it to iPSCs. iPSCs are grown for therapeutic use on patients. iPSCs can be used to produce gametes, where the latter have the same potential and functions as naturally grown gametes. However, the case has not been made that research on iPSCs would even come close to leading to the selection or enhancement of future human beings. Hence, iPSC researchers are not conducting arbitrary or disproportionate experiments on the embryonic origins of human beings, and thus they are not infringing on the sphere that Habermas regards as sacrosanct. In support of this claim, we can adduce an argument from potential and an argument from function. Habermas’s argument can only plausibly be extended to research on iPSCs if we introduce rather strong assumptions – namely, that research on iPSCs is a form of arbitrary experimentation, without making essential distinctions, particularly regarding the origins of human life. The main difference between iPSCs and ESCs concerns the source of iPSCs: while ESCs are extracted from a human embryo, iPSCs derive from somatic cells of adults. Nevertheless, it cannot be ruled out that iPSCs will one day play a role in a process that will lead to the creation of embryos. While this point seems quite far from Habermas’s original contentions, this is not to say that research on iPSCs is completely innocuous.